THU0383 Is There A Difference between the Western and Eastern Turkish Familial Mediteranean Fever Patients?. (10th June 2014) - Sari, I.; Solmaz, D.; Cetin, P.; Ozturk, S.; Basoglu, T.; Tunca, M.
Abstract : Background: The prevalence of familial mediterranean fever (FMF) is relatively lower in western regions of Turkey compared with Eastern Anatolia. Likewise, the disease is quite uncommon in Greece and other Balkan countries. It is also presumed that patients from Eastern Anatolia have more severe phenotypic expression. If this presumption is relevant, underdetection of milder cases would contribute to observed distribution of FMF. Objectives: To compare the clinical and genetical characteristics of our patients according to their ancesteral origins. Methods: Among the 698 adult FMF patients registered in the computer files of our institute there were 214 cases whose ancestors were either strictly from Balkan countries and coastal regions of Eagean Sea (n=129) or Eastern Anatolia (n=85). Patients with mixed ancestors were not included. The following data were analyzed: age, disease duration, delay of diagnosis, genotype status, attacks despite colchicine, presence of fever, abdominal pain, pleuritic pain, arthritis, erysipelas-like erythema, amyloidosis and inflammatory back pain. Results: Clinical features such as attacks despite colchicine, amyloidosis, protracted febrile myalgia, and delay in diagnosis were similar between the groups (table 1 ). Genotype analyses were available in 170 patients (76.9%). Four founder mutations (M694V, E148Q, V726A, M680I) were searched for every genotyped patient. 5.29% of the patients (n=9) were having wild type mutations. Allelic frequencies of the mutations were as follows: 46.8 for M694V, 13.8 for M680I, 10.6 for V726A, and 5.9 for E148Q. Comparison of the eastern and western patients revealed no difference between the groups according to the mutations (table 1 ). Conclusions: The comparison of the western and eastern Turkish FMF patients revealed no statistically significant difference regarding to their clinical, demographical and genotype status. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.2018